Enhancing Product-Market Fit through CustDev: A Regional Perspective on Startup Development - Bogdanov, Anvar (Scientific Journal of Bielsko-Biala School of Finance and Law, 2025)
Obtaining product-market fit continues to make the difference in the success or failure rate of startups, especially in a regulated and competitive industry like Germany. It is a study of how customer development strategies help to understand product-market fit in a region of an entrepreneur ecosystem. With a real-world case based on market research of water purification salt, which has been identified as a high-demand product depending on the Industrial and municipal sectors, the research combines both qualitative perspectives with a quantitative econometric method. The surveys used were 47 structured customer interviews and regional ecosystem measurements between 2022 and 2024. The influence of CustDev intensity and quality, market potential, supplier access, import margins, regulatory constraints, and support mechanisms on product-market fit outcomes was evaluated by means of a logistic regression model. Important observations note that CustDev_Intensity (b = 0.345, p < 0.01), CustDev_Quality (b = 0.567, p < 0.001), and Supply_Access (b = 1.130, p < 0.001) have a significant positive effect on the likelihood of product-market fit, whereas Founder_Constraints (b = -1.125, p < 0.001) hamper performance.